Terapi Aktivitas Kelompok Stimulasi Sensori terhadap Kemampuan Memberi Respons Pasien Skizofrenia yang Mengalami Halusinasi - I Wayan Candra (Jurnal Gema Keperawatan, 2013)
The purpose of this research were to know the influence group aktivity therapy stimulation sensori to ability respons for client Skizofrenia with hallusination.This type of study is pre experimental design in this study using the One-group pre-test-posttest design with a sample of 15 people. The sampling tecniq with use Quota Sampling. Type of data is primary data. Results the ability to respond schizophrenia patients who experienced hallucinations before given sensory stimulation therapy group activity most that 9 people (60%) in the low category, after being given sensory stimulation therapy group activity most that 10 people (66.7%) in the either category of test results obtained Wilcoxon signed rank test P = 0.000 of 0.01 means that there is a very significant influence group activity therapy sensory stimulation on the ability of responding patients who experienced hallucinations in schizophrenia Sahadev Space Bali Provincial Mental Hospital in 2013.